Early Science Literacy: Fostering Scientific Thinking Through Play-Based Learning in Early Childhood Education - Maria Fatima Mardina Angkur (Yayasan Adra Karima Hubbi, 2025)
Background. The development of science literacy in early childhood lays the foundation for critical thinking, inquiry skills, and lifelong learning. Traditional approaches to science education often overlook the unique cognitive and developmental needs of young learners. Recent pedagogical shifts suggest that play-based learning may offer an effective pathway to foster scientific thinking in early childhood education. Purpose. This study investigates how play-based strategies support the development of early science literacy among preschool-aged children. The research employed a qualitative case study design involving three early childhood education centers that integrated science themes into daily play activities. Method. Data were collected through classroom observations, educator interviews, and children’s learning artifacts, then analyzed thematically to identify patterns of inquiry and conceptual understanding. Results. Findings revealed that play-based environments encouraged curiosity, hypothesis generation, experimentation, and early evidence-based reasoning. Children demonstrated an emerging understanding of scientific concepts such as cause and effect, classification, and environmental awareness through guided exploratory play. Conclusion. The study concludes that play-based learning serves as a powerful pedagogical approach for nurturing early science literacy. It recommends intentional integration of scientific exploration into play curricula to promote cognitive engagement and scientific habits of mind in early learners.